Antibacterial and anti-biofilm properties of Aptosimum albomarginatum (Marloth & Engl.) and Dicoma schinzii (O. Hoffm.) crude methanolic extracts against S. aureus and MRSA. - Walter, Sunette.; Böck, Ronnie (Namibian Journal for Research, Science and Technology, 2022)
Background: The effectiveness of phytomedicine is often questioned by scientists. This study therefore aimed to test crude methanolic extracts from two traditional medicinal plants currently being used in Namibia for their antibacterial and anti-biofilm activity against Staphylococcus aureus and methicillin-resistant S. aureus (MRSA). Materials and methods: Aptosimum albomarginatum (Marloth & Engl.) roots and Dicoma schinzii (O. Hoffm.) roots and leaves were used to prepare crude methanolic extracts by maceration, filtration, rotary evaporation and freeze-drying. Thin layer chromatography (TLC) was used to detect flavonoids, saponins and anthraquinones in the plant material. For antibacterial activity, two S. aureus reference strains (one susceptible and one multi-drug resistant MRSA) and 10 S. aureus nasal isolates from school children were used in disk diffusion assays with crude methanolic plant extracts. The microtiter plate assay with crystal violet stain was used to determine if these extracts could inhibit and/or eradicate bacterial biofilms. Results: Aptosimum albomarginatum root extract displayed moderately antibacterial activity against five nasal isolates (one MRSA isolate) and two reference strains, of which one was multi-drug resistant MRSA. This extract was also the best biofilm inhibition agent, with highly active inhibition (86.0%) observed in S. aureus ATCC 33591 (MRSA). Dicoma schinzii root extract had moderate antibacterial activity against six nasal isolates and the two reference strains; its leaf extract was moderately active against two nasal isolates. The D. schinzii leaf extract moderately inhibited biofilms in two nasal isolates and S. aureus ATCC 25923. Flavonoids and saponins detected in both the roots and leaves of the two plants may have contributed to the extracts’ antibacterial and antibiofilm activity. Conclusion: Aptosimum albomarginatum roots and D. schinzii roots and leaves displayed anti-staphylococcal activity, indicating potential use against staphylococcal infections involving the bacteria under study. Noteworthy is both antibacterial and anti-biofilm properties of A. albomarginatum root extract against MRSA.